1999
DOI: 10.1103/physrevb.60.4450
|View full text |Cite
|
Sign up to set email alerts
|

Auger effect as the origin of the fast-luminescent band of freshly anodized porous silicon

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…The decrease in relaxation time and the simultaneous formation of the Pauli-plateau strongly suggests an interplay between faster carrier relaxation and occupation of multiexcitonic states 25 . For τ r it is found that the data points follow a P −0.67±0.02 dependency strongly indicating that Auger processes mediate intersublevel relaxation 26 . This observation constitutes strong evidence that the occupation of the dot with multiple carriers mediates faster carrier capture and energy relaxation.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…The decrease in relaxation time and the simultaneous formation of the Pauli-plateau strongly suggests an interplay between faster carrier relaxation and occupation of multiexcitonic states 25 . For τ r it is found that the data points follow a P −0.67±0.02 dependency strongly indicating that Auger processes mediate intersublevel relaxation 26 . This observation constitutes strong evidence that the occupation of the dot with multiple carriers mediates faster carrier capture and energy relaxation.…”
mentioning
confidence: 86%
“…This behaviour suggests a power-dependent change of the carrier capture and inter-sublevel relaxation times which are typically governed by Auger-like processes or LO-phonon emission in QDs 25 and will be discussed in relation to figures 3c and 4 below. The ultraslow carrier relaxation time for P = 0.48 W/cm 2 indicates the presence of an intrinsic phonon bottleneck 8 that, for stronger excitation levels, is masked by much faster carrier capture and relaxation via Auger-like processes with other charge carriers in the near vicinity of the quantum dot 26 . In similar off-chip detected time-resolved PL experiments, τ r typically is ≤ 100 ps 25 and does not show any indications of a bottleneck.…”
mentioning
confidence: 99%
“…For sample B the power coefficient b is found to be very close to 2/3 ͑b = 0.72Ϯ 0.01͒, which is the signature of a three particle Auger recombination mechanism. 29 Although emission from sample B is more intense ͓triangle-dotted line in Fig. 4͑a͔͒, the power coefficient is higher for sample A ͑b = 0.83Ϯ 0.05͒.…”
Section: Visible Pl Spectroscopymentioning
confidence: 99%
“…3, a very fast decay ͑first few microseconds͒ is observed which is attributed to Auger recombination within the nanoparticle. 29 To check this hypothesis, we have measured the visible PL intensity of samples A and B as a function of excitation photon flux ⌽. The results are reported in Fig.…”
Section: Visible Pl Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation